Prediction of optimum welding parameters for FSW of aluminium alloys AA6063 and A319 using RSM and ANN. (2018) - Muthu Krishnan, M.; Maniraj, J.; Deepak, R.; Anganan, K.
Abstract: Friction stir welding (FSW) is an innovative solid state joining technique and has been employed in industries for joining aluminum, magnesium, zinc and copper alloys. The FSW process parameters such as tool, rotational speed, welding speed, axial force, etc play major role in deciding the weld quality. A mathematical modeling was developed based on experiments conducted using central composite circumscribed design and is compared using ANN methodology to predict the tensile strength of dissimilar FSW aluminum alloys. It was found the error rate predicted the regression ANN was smaller than predicted by the other ANN methods.